The Gift of Oneself from the Perspective of New Readings of “The Gift” by Marcel Mauss - Malatesta Freitas Maria Do Socorro (Journal for Perspectives of Economic Political and Social Integration, 2014)
The Gift: Forms and Functions of Exchange in Archaic Societies, by Marcel Mauss, is an important reference in Social Sciences for thinking about the theme of the gift, proposed in this congress. This brief work has as goal to present a rereading of The Gift by contemporary authors that try to think today’s society under this perspective. It’s a literature review of books and articles by Allain Caillé, Jacques Godbout and some Brazilian authors: Eric Sabourin, Marcos Lanna, Paulo Henrique Martins and Jorge Luiz Villela.